Rhizosphere modelling reveals spatiotemporal distribution of daidzein shaping soybean rhizosphere bacterial community. (2nd January 2020) - Okutani, Fuki; Hamamoto, Shoichiro; Aoki, Yuichi; Nakayasu, Masaru; Nihei, Naoto; Nishimura, Taku; Yazaki, Kazufumi; Sugiyama, Akifumi
Abstract: Plant roots nurture a wide variety of microbes via exudation of metabolites, shaping the rhizosphere's microbial community. Despite the importance of plant specialized metabolites in the assemblage and function of microbial communities in the rhizosphere, little is known of how far the effects of these metabolites extend through the soil. We employed a fluid model to simulate the spatiotemporal distribution of daidzein, an isoflavone secreted from soybean roots, and validated using soybeans grown in a rhizobox. We then analysed how daidzein affects bacterial communities using soils artificially treated with daidzein. Simulation of daidzein distribution showed that it was only present within a few millimetres of root surfaces. After 14 days in a rhizobox, daidzein was only present within 2 mm of root surfaces. Soils with different concentrations of daidzein showed different community composition, with reduced α‐diversity in daidzein‐treated soils. Bacterial communities of daidzein‐treated soils were closer to those of the soybean rhizosphere than those of bulk soils. This study highlighted the limited distribution of daidzein within a few millimetres of root surfaces and demonstrated a novel role of daidzein in assembling bacterial communities in the rhizosphere by acting as more of a repellant than an attractant. Abstract : We used a forward genetics approach to isolate and characterize an Arabidopsis Cd‐sensitive mutant, Cd‐induced short root 1 (cdsr1), which has a point mutation in the protein phosphatase 2A (PP2A) subunit 4C. The mutant overproduced ethylene in response to Cd. PP2A alleviates Cd‐induced growth inhibition by modulating ethylene production, likely through dephosphorylation of 1‐aminocyclopropane‐1‐carboxylic acid synthases. Our study sheds light on the regulation of ethylene production in response to Cd stress.